2020
DOI: 10.30650/jem.v14i1.1288
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Management Leadership Style: Transformational or Transactional?

Abstract: The purpose of this study was to analyze the effect of transformational and transactional leadership style on the performance of the latest version of the FSSC 22000 (Food Safety System Certification) food safety management system, version 5 of 2019 in the food industry in Tangerang. The object of the research were employees in several food industries that worked in the Tangerang City area who had implemented FSSC 22000 version 5 2019; as many as 120 people, and data collection method was done by giving out el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to the authors, while transformational leadership is acknowledged as an effective approach, the call for a harmonious balance between transformational ideals and structured, task-oriented methodologies reverberates in organizational efficiency and effectiveness. Purwanto (2021) underscores the effectiveness of a multifaceted leadership approach that integrates transformational qualities with transactional elements within the educational context. The symbiotic relationship between these leadership attributes is instrumental in yielding superior outcomes, enhancing both teaching and learning experiences.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, while transformational leadership is acknowledged as an effective approach, the call for a harmonious balance between transformational ideals and structured, task-oriented methodologies reverberates in organizational efficiency and effectiveness. Purwanto (2021) underscores the effectiveness of a multifaceted leadership approach that integrates transformational qualities with transactional elements within the educational context. The symbiotic relationship between these leadership attributes is instrumental in yielding superior outcomes, enhancing both teaching and learning experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, narrow the gap to achieve global goals such as Goal 11 of sustainable cities and communities in the medical sector. Amiri et al ( 2015 ) and Hutagalung and Yanthy ( 2020 ) opined that Environmental Management Systems increase organisation’s environmental accountability and employees’ knowledge towards environmental management and performance. This suggests that attaching of Environmental Management Systems enables medical facilities to be responsible for solid waste they generate, instead of waiting for municipalities.…”
Section: Opportunities Associated With Integration Of Environmental M...mentioning
confidence: 99%
“…Consequently, medical waste management procedures are carried out aptly owing to proper sharing of information among those responsible for waste management at workplace. Asbari et al ( 2019 ) and Hutagalung and Yanthy ( 2020 )opined that workers’ performance and morale is boosted if ISO 45001 system is pinned to company’s management system since it supports work safety of employees. This revealed that Environmental Management Systems play a pivotal role in reducing occupational hazards associated with activities involved in management waste within the medical sector.…”
Section: Opportunities Associated With Integration Of Environmental M...mentioning
confidence: 99%
See 1 more Smart Citation